HUBUNGAN UPAYA KESEHATAN SEKOLAH DENGAN PERILAKU HIDUP BERSIH DAN SEHAT PADA SISWA KELAS IV, V, VI SDN 043936 MERK SITUNGALING TAHUN 2018 - Rizka Annisa; Herlina J. EL-Matury; Elmina Tampubolon (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2018)
Ginting, Elisabet. Relationship between School Health Business (UKS) and Clean and Healthy Living Behavior (PHBS) for IV, V, VI class students from SDN 0 3936 Brand Situngaling. Thesis of the Department of Public Health, Faculty of Public Health, Deli Husada Deli Tua Health Institute (Supervision Ns. Nurmala Sari, SST, M.Kes) The method used is the analytical correlation with a transversal approach. The population of this study consisted of grade IV, V, V1 students in SDN 043936, for a total of 56 students sampled by simple random sampling technique. The independent variables in this study were the role of School Health Companies (UKS) and the dependent variable was the application of Clean and Healthy Living Behavior (PHBS) in grades IV, V, VI. Data collection via questionnaire. Data processing by editing, coding, scoring and tabulation with the Spearman Rank statistical test. The results of this study indicate that 56 respondents who performed well in the UK were 56 respondents (26.8%), while nearly half of the PHBS respondents were up to 15 respondents (6.9%). Sperman Rank test results obtained pylt; 0.05, p = 0.013, so H1 was accepted. The conclusion of this study is that there is a relationship between the role of the School Health Unit (UKS) and the implementation of clean and healthy behavior (PHBS) in students of grades IV, V, VI. Schools are expected to suggest that schools can increase UKS activities to raise student awareness of the importance of PHBS.